Atividades práticas de física e motivação: uma abordagem didático-pedagógica - Holz, Sheila Magali (2021)
We investigated the use of practical activities that, in addition to their pedagogical didactic function, help to promote the motivation of students in the discipline of Physics, in the second year of high school. The research was carried out at a Federal Public College, in seven classes (three in 2017 and four in 2018). The theoretical contribution that guided the research consisted of studies by several authors regarding the use of experimental activities and about motivation. Aiming to know how experimental activities are being addressed in the specialized literature, we carried out a literature review that included articles published in the Brazilian Journal of Physics Education in the period between 2002 and 2017. We found 138 articles on this topic, of which only 17 were intended for high school. In order to develop practical activities that play, in addition to the pedagogical function, the role of encouraging students' motivation in the subjects studied in the discipline of Physics, we use an approach based on Educational Design Research. Based on this conception of research, which is used to solve practical problems in real contexts, through a cyclical process of analysis and exploration, design and construction, and evaluation and reflection, we developed our investigation. To make it clearer, more practical and enable a more holistic view of our work, we developed a Panoramic Operational Matrix, which allows, after carrying out the activities, based on the observations and notes in the logbook, to propose changes for the following activities in the same year (with different content) or in the same activity that will be implemented next year. With this direction, we implemented practical activities in 2017, the results of which are presented. At the end of that school year, students answered a questionnaire, referring to the eight practical activities developed, which was composed of eight open questions. Through this, we seek to know more deeply the opinions of students regarding the performance of practical activities, whose analysis was carried out using Content Analysis designed by Bardin (2007). Based on the analyses, the observations made during the activities, the logbook notes and the analysis of the questionnaire, we redesigned the eight activities and these were implemented again in 2018, following the same system as the previous year. We carried out an individual analysis of each of the eight activities, based on the students' opinions on these, and a comparison between the 2017 and 2018 activities. We also investigated the Motivation and Efficiency of the different Teaching Strategies used by teachers, based on the students' opinion of 2018. With the analysis of the final categories from the questionnaires answered by the students, we present the design principles that should be considered in the preparation of practical activities so that these, in addition to their pedagogical function, also foster the motivation of students to study the discipline of physics.